2011
DOI: 10.1097/inf.0b013e3182054ab9
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of an Investigational Quadrivalent Meningococcal ACWY Tetanus Toxoid Conjugate Vaccine in Healthy Adolescents and Young Adults 10 to 25 Years of Age

Abstract: The investigational MenACWY-TT vaccine was immunogenic in adolescents and young adults, with an acceptable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 18 publications
5
43
0
3
Order By: Relevance
“…The safety profile of MenACWY-TT was comparable to that observed in previous studies conducted with adolescents and young adults (42,43). However, a lower incidence of pain at the injection site was observed in two other studies, one conducted with adolescents from India, Taiwan, and the Philippines (26.2%) (44) and the other with adults from Lebanon and the Philippines (19.4%) (36).…”
Section: Discussionsupporting
confidence: 81%
“…The safety profile of MenACWY-TT was comparable to that observed in previous studies conducted with adolescents and young adults (42,43). However, a lower incidence of pain at the injection site was observed in two other studies, one conducted with adolescents from India, Taiwan, and the Philippines (26.2%) (44) and the other with adults from Lebanon and the Philippines (19.4%) (36).…”
Section: Discussionsupporting
confidence: 81%
“…52 Another phase II randomized controlled study was conducted on 872 subjects aged 10-25 years to assess the immunogenicity of MenACWY-TT using the quadrivalent MenACWY-DT as a comparator. 53 Results confirmed that MenACWY-TT was immunogenic in healthy subjects aged 11 to 25 years. When results in 10 year old children for each serogroup were compared, 83% of the MenACWY-TT group and 70.7% the MenACWY-DT group had hSBA titers 1:4.…”
Section: Immunogenicity Of Menacwy-ttsupporting
confidence: 73%
“…MenACWY-TT aşısının çocuk, adolesan, erişkin ve 55-103 yaş arası popülasyonda da immünojenik ve güvenilir olduğu yapılan çalışmalarda gösterilmiştir (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) . Baxter ve ark.…”
Section: Menacwy-tt Ile Ilgili Yürütülen Antikor Sürekliliğiunclassified
“…Baxter ve ark. 'nın (29) çalışmasında, 10-25 yaş arası adolesan ve genç erişkinlerde tek doz MenACWY-TT aşısının immünojenik ve güvenilir olduğu saptanmıştır. Benzer şekilde 11-55 yaş arası çocuk ve erişkinlerde de tek doz aşının immünojenik ve güvenilir olduğu bildirilmektedir (22) .…”
Section: Menacwy-tt Ile Ilgili Yürütülen Antikor Sürekliliğiunclassified